2022
DOI: 10.1128/mbio.03239-21
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphoinositide-Binding Protein Acts in the Trafficking Pathway of Hemoglobin in the Malaria Parasite Plasmodium falciparum

Abstract: Malaria represents an enormous burden for a significant proportion of humanity and the lack of vaccines and problems with drug resistance to all antimalarials demonstrate the need to develop new therapeutics. Inhibitors of phosphoinositide metabolism are currently being developed as antimalarials but our understanding of this biological pathway is incomplete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 136 publications
(179 reference statements)
0
14
0
Order By: Relevance
“…The molecular effectors involved in this process remain poorly characterized and so far only VPS45 [44], the phosphoinositide-binding protein PX1 [45], the host enzyme peroxiredoxin 6 [46] and K13 and some of its compartment proteins (Eps15, AP2µ, KIC7, UBP1) [26] have been reported to act at different steps in the endocytic uptake pathway of hemoglobin. While inactivation of VPS45, PX1 or actin resulted in an accumulation of hemoglobin filled vesicles [43][44][45], indicative of a block during endosomal transport, no such vesicles were observed upon inactivation of K13 and its compartment proteins [26], suggesting a role of these proteins during initiation of endocytosis. In previous work we used a quantitative BioID approach to identify proteins in close proximity to K13 and its interactor Eps15 [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular effectors involved in this process remain poorly characterized and so far only VPS45 [44], the phosphoinositide-binding protein PX1 [45], the host enzyme peroxiredoxin 6 [46] and K13 and some of its compartment proteins (Eps15, AP2µ, KIC7, UBP1) [26] have been reported to act at different steps in the endocytic uptake pathway of hemoglobin. While inactivation of VPS45, PX1 or actin resulted in an accumulation of hemoglobin filled vesicles [43][44][45], indicative of a block during endosomal transport, no such vesicles were observed upon inactivation of K13 and its compartment proteins [26], suggesting a role of these proteins during initiation of endocytosis. In previous work we used a quantitative BioID approach to identify proteins in close proximity to K13 and its interactor Eps15 [26].…”
Section: Introductionmentioning
confidence: 99%
“…Hemoglobin trafficking to the parasite food vacuole is believed to be initiated at membrane invaginations called cytostomes [27,33,39] followed by vesicular transport from the parasite plasma membrane (PPM) to the food vacuole [33,40], likely in an actin-myosin motor dependent manner [39,[41][42][43]. The molecular effectors involved in this process remain poorly characterized and so far only VPS45 [44], the phosphoinositide-binding protein PX1 [45], the host enzyme peroxiredoxin 6 [46] and K13 and some of its compartment proteins (Eps15, AP2µ, KIC7, UBP1) [26] have been reported to act at different steps in the endocytic uptake pathway of hemoglobin. While inactivation of VPS45, PX1 or actin resulted in an accumulation of hemoglobin filled vesicles [43][44][45], indicative of a block during endosomal transport, no such vesicles were observed upon inactivation of K13 and its compartment proteins [26], suggesting a role of these proteins during initiation of endocytosis.…”
mentioning
confidence: 99%
“…Although we occasionally observe MyoI at or around the BC of extracellular parasites, MyoI foci are widely distributed throughout the cytoplasm, which therefore, only partly supports this hypothesis and needs further attention in the future (Figure 3B) . An additional, more puzzling observation is found in the TgBCC9 ortholog in P. falciparum, named PfPH2, which was associated with a role in microneme exocytosis and localizes to the apical end (Ebrahimzadeh et al, 2019;Mukherjee et al, 2022). As evident from the data assembled here, endocytosis of extracellular parasites might play out at the basal end rather than at the apical end and could be mechanistically related to the microneme secretion defect observed upon coronin depletion in T. gondii (Salamun et al, 2014).…”
Section: Motilitymentioning
confidence: 67%
“…The gene knockout of Plasmodium-specific putative phosphoinositide-binding protein (PfPX1) was found to affect the haemoglobin trafficking pathway and made the parasite ART-resistant, suggesting that the haemoglobin trafficking pathway is an essential process for the ART-resistance mechanism. It was also shown that PfPX1 binds to phosphatidylinositol-3-phosphate (PI3P), a molecule that has already been shown to be affected by K13 mutation [15,24]. Taken together, different Fd and ARPS10 alleles might affect the isoprenoid synthesis pathway that leads to insufficient substrates for vesicle formation, especially the haemoglobin vesicular trafficking pathway which is also affected by the K13 mutation and consequently enhances parasite ART-resistance.…”
Section: Discussionmentioning
confidence: 99%